2017
DOI: 10.3389/fpls.2017.00687
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptomic Identification of Drought-Related Genes and SSR Markers in Sudan Grass Based on RNA-Seq

Abstract: Sudan grass (Sorghum sudanense) is an annual warm-season gramineous forage grass that is widely used as pasture, hay, and silage. However, drought stress severely impacts its yield, and there is limited information about the mechanisms of drought tolerance in Sudan grass. In this study, we used next-generation sequencing to identify differentially expressed genes (DEGs) in the Sudan grass variety Wulate No.1, and we developed simple sequence repeat (SSR) markers associated with drought stress. From 852,543,826… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 56 publications
1
10
2
1
Order By: Relevance
“…Using transcriptome data resources, rapid progress in the development of SSR loci has been made in many green plant species [ 9 ]. Recently, a large amount of SSR markers were developed in forage and turfgrass crops such as perennial ryegrass [ 10 ], Italian ryegrass [ 11 ], alfalfa [ 12 ], hemarthria [ 13 ], red clover [ 14 ], orchardgrass [ 15 ], sudangrass [ 16 ], common bermudagrass [ 17 ], creeping bentgrass [ 18 ], seashore paspalum [ 19 ], and zoysiagrass [ 20 ]. To date, there is not a large quantity of SSR markers developed in centipedegrass, with the exception of a recent report on EST-SSR development from a cold-stressed transcriptome of centipedegrass [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using transcriptome data resources, rapid progress in the development of SSR loci has been made in many green plant species [ 9 ]. Recently, a large amount of SSR markers were developed in forage and turfgrass crops such as perennial ryegrass [ 10 ], Italian ryegrass [ 11 ], alfalfa [ 12 ], hemarthria [ 13 ], red clover [ 14 ], orchardgrass [ 15 ], sudangrass [ 16 ], common bermudagrass [ 17 ], creeping bentgrass [ 18 ], seashore paspalum [ 19 ], and zoysiagrass [ 20 ]. To date, there is not a large quantity of SSR markers developed in centipedegrass, with the exception of a recent report on EST-SSR development from a cold-stressed transcriptome of centipedegrass [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomic analysis is an effective approach to identify drought stress related genes, pathways, and processes. The studies on molecular mechanisms of drought tolerance using transcriptomic analysis have been reported extensively in many plants [ 15 20 ], including wheat [ 21 ], wild emmer wheat [ 22 , 23 ] and wild barley [ 24 , 25 ]; however, little is known about the Tibetan hulless barley. Recently, Zeng et al demonstrated changes in the gene expression patterns of well-watered, water deficit, and final water recovery stages in hulless barley.…”
Section: Introductionmentioning
confidence: 99%
“…5; Table S1). It is known that different varieties have different conditions so that they can yield different classifications [25]. We may find some useful genes in V class (defense mechanisms) of salt-stress buckwheat.…”
Section: Resultsmentioning
confidence: 99%